Effects of inspiratory muscle training in COPD patients: A systematic review and meta‐analysis. (23rd May 2018) - Beaumont, Marc; Forget, Patrice; Couturaud, Francis; Reychler, Gregory
Abstract: Objectives: In chronic obstructive pulmonary disease (COPD), quality of life and exercise capacity are altered in relationship to dyspnea. Benefits of inspiratory muscle training (IMT) on quality of life, dyspnea, and exercise capacity were demonstrated, but when it is associated to pulmonary rehabilitation (PR), its efficacy on dyspnea is not demonstrated. The aim of this systematic review with meta‐analysis was to verify the effect of IMT using threshold devices in COPD patients on dyspnea, quality of life, exercise capacity, and inspiratory muscles strength, and the added effect on dyspnea of IMT associated with PR (vs. PR alone). Study selection: This systematic review and meta‐analysis was conducted on the databases from PubMed, Science direct, Cochrane library, Web of science, and Pascal. Following key words were used: inspiratory, respiratory, ventilatory, muscle, and training. The searching period extended to December 2017. Two reviewers independently assessed studies quality. Results: Forty‐three studies were included in the systematic review and thirty‐seven studies in the meta‐analysis. Overall treatment group consisted of six hundred forty two patients. Dyspnea (Baseline Dyspnea Index) is decreased after IMT. Quality of life (Saint George's Respiratory Questionnaire), exercise capacity (6 min walk test) and Maximal inspiratory pressure were increased after IMT. During PR, no added effect of IMT on dyspnea was found. Conclusion: IMT using threshold devices improves inspiratory muscle strength, exercise capacity and quality of life, decreases dyspnea. However, there is no added effect of IMT on dyspnea during PR (compared with PR alone).